Fingerprint: A Unique and Reliable Method for Identification - Bose, Palash Kumar; Kabir, Mohammad Jubaidul (Journal of Enam Medical College, 2017)
Fingerprints have been the gold standard for personal identification within the forensic community for more than one hundred years. It is still universal in spite of discovery of DNA fingerprint. The science of fingerprint identification has evolved over time from the early use of finger prints to mark business transactions in ancient Babylonia to their use today as core technology in biometric security devices and as scientific evidence in courts of law throughout the world. The science of fingerprints, dactylography or dermatoglyphics, had long been widely accepted, and well acclaimed and reputed as panacea for individualization, particularly in forensic investigations. Human fingerprints are detailed, unique, difficult to alter, and durable over the life of an individual, making them suitable as lifelong markers of human identity. Fingerprints can be readily used by police or other authorities to identify individuals who wish to conceal their identity, or to identify people who are incapacitated or deceased, as in the aftermath of a natural disaster J Enam Med Col 2017; 7(1): 29-34